Retratos de si: a autorrepresentação nos álbuns virtuais na era Instagram - Custodio Júnior, Francisco Jose (2017)
The objective of this study is to reflect on self-portrait photography, historically known as self-portrait, so explored by professional and renowned photographers, artists, personalities and ordinary people. It seeks to understand the relationship between photography and memory in the universe of technology and digital communication, social media and media applications in contemporary society. This reflection culminated in the realization of photography workshops with the school community of the city of Uberlandia/MG., where we propose to discuss the history of photography and the elementary processes of production as well as its contemporary mass through social networks. And the result of the realization of printed photographic exhibition and also the sharing of selfies images in virtual albums of social media.